Being Jewish After the Destruction of Gaza - Beinart, Peter (London: Atlantic Books, 2025)
"In Peter Beinart's view, one story has long dominated Jewish communal life: that of persecution and victimhood. It is a story that erases much of the nuance of sacred Jewish tradition and history, and also warps our understanding of modern history. After Gaza, where Jewish texts, history, and language have been deployed to justify mass slaughter and starvation, he argues, Jews must tell a new story. After this war, whose horror will echo for generations, they must do nothing less than offer a new answer to the question: What does it mean to be a Jew? Beinart imagines an alternate story that would draw on other nations' efforts at moral reconstruction and a different reading of Jewish history. A story in which Jews have the right to equality, not supremacy, and in which Jewish and Palestinian safety are not mutually exclusive but intertwined. One in which we inhabit a world that recognizes the infinite value of all human life, beginning in the Gaza Strip. Being Jewish After the Destruction of Gaza is a provocative and fearless argument that will expand and inform one of the defining conversations of our time. It is a book that only Peter Beinart could write: a passionate yet measured work that brings together his personal experience, his commanding grasp of history, his keen understanding of political and moral nuance, and a clear vision for the future"-- Provided by publisher
Prologue: We need a new story -- 1. They tried to kill us, we survived, let's eat --2. To whom evil is done -- 3. Ways of not seeing -- 4. The new new Antisemitism -- 5. Korach's Children
Keywords: October 7 Hamas Attack, Israel, 2023--Influence; Israel-Hamas War, 2023---Influence